Lysine supplementation for growing-finishing swine rations - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1969)
The protein level and protein quality of swine rations consisting primarily of grain can be changed by adding either protein like soybean meal or individual amino acids like lysine. Protein requirements are based on individual amino acids that compose the protein. Amino acid most lacking in grain proteins is lysine, so lysine is the most limiting amino acid in growing-finishing rations made up primarily of grain. Feeding trials reported here were designed to: (1) compare corn and sorghum grain, (2) determine the value of 0.1% of lysine added to the ration, (3) compare performance of barrows and gilts and (4) determine feeder space needed.; Swine Day, Manhattan, KS, September 25, 1969
Keywords: Swine day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 151; Swine; Growing-finishing rations; Protein; Lysine